2010
DOI: 10.1007/s00035-010-0076-y
|View full text |Cite
|
Sign up to set email alerts
|

Plant species’ range shifts in mountainous areas—all uphill from here?

Abstract: Species from many different habitats are responding to recent climate change. Mountainous areas are of particular interest as they provide pronounced gradients and have experienced above-average temperature increases. Data from the beginning of the 20th century of both the upper and lower range limits of plants of the European Alps were updated a century later and analyzed in order to identify common trends and deviating patterns of shifts at opposing ends of species' ranges. At the upper limit, there was a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 45 publications
2
51
1
1
Order By: Relevance
“…In the eastern Himalaya, Telwala et al (2013) reported 87 % of endemic plants (out of 124 species) shifted upslope in response to a temperature rise in mean summer temperature of 0.76 and 3.65°C in mean winter temperature. Over the last nine decades, an average upslope shift of 145 m was reported in Engadine valley of Swiss Alps (Frei et al 2010) and in the last half century a 70 m elevational shift in the Montseny Mountains (Catalonia, NE Spain) was reported (Penuelas et al 2007) as a response to global warming.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the eastern Himalaya, Telwala et al (2013) reported 87 % of endemic plants (out of 124 species) shifted upslope in response to a temperature rise in mean summer temperature of 0.76 and 3.65°C in mean winter temperature. Over the last nine decades, an average upslope shift of 145 m was reported in Engadine valley of Swiss Alps (Frei et al 2010) and in the last half century a 70 m elevational shift in the Montseny Mountains (Catalonia, NE Spain) was reported (Penuelas et al 2007) as a response to global warming.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al 2011;Lenoir et al 2008;Telwala et al 2013), making it difficult to determine the role played by climate in any changed scenario. The upslope shift for different species ranged from 586 to 787 m on the Chimborazo volcano in Ecuador over a 210-year period (MoruetaHolme et al 2015); in the Engadine valley of Swiss Alps, more than 100 m upslope shift has been reported during the last nine decades (Frei et al 2010) and 87 percent of 124 endemic plants species have expanded their range in Sikkim Himalaya during the last ca. 150 years (Telwala et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Mountain regions tend to warm more rapidly than the northern hemisphere average (Rebetez & Reinhard, 2008) and the rate of warming in mountains is expected to be up to three times higher than the global average rate of warming Over the last 20 years, several studies comparing recent survey data with historical data from the early 20th century documented an increase in species numbers on high mountain summits of the European Alps (Kammer et al, 2007). Frei et al (2010) investigated 25 summits in the Swiss Alps and compared their results with data originating from the beginning of the 20th century (Rübel, 1912;Braun, 1913 significant increase in the mean number of summits colonized by each species during the 20th century. A mean upward shift of +145.3 m of the studied species was identified, which underlines the upward trend of upper range margins.…”
Section: The Alps and Switzerlandmentioning
confidence: 99%
“…Migration to higher elevation in response to climate change, as observed in other alpine plants (e.g. Frei et al 2010), might be too slow or limited in C. thyrsoides because suitable grassland habitats in the Alps are shrinking as a consequence of abandonment or overgrazing ). The study region is called ''Schynige Platte'' and is a small mountain (centered at 46°39 0 12 00 N; 7°54 0 42 00 E) in the northern Swiss Alps, consisting of calcareous bedrock.…”
Section: Study Species and Regionmentioning
confidence: 99%